The oxidation behavior of a ductile Hf0.5Nb0.5Ta0.5Ti1.5Zr refractory high-entropy alloy in pure oxygen condition at 500–900 °C - Y.Z. Wang; N. Gao; X.W. Liu; W.M. Chen; H.T. Zheng (Journal of Materials Research and Technology, 2023)
In this study, the oxidation behavior of Hf0.5Nb0.5Ta0.5Ti1.5Zr refractory high-entropy alloy (RHEA) was investigated at temperature range of 500–900 °C in pure oxygen condition, and the oxidation mechanism was systemically discussed. The oxidation kinetics curve shows linear lines with the initially slow and subsequently faster oxidation rate at 700 °C. As the oxidation temperature increased to 800 °C, the oxidation curve comprises three stages: beginning linear lines, intermediate breakaway platform and final parabola. In addition, the oxidation kinetics curves exhibit near parabolic in all the studied temperature. The oxygen diffusion was considered as the predominant mechanism in the oxidation of RHEA.